Effects of Sleep Extension on Inhibitory Control in Children With ADHD: A Pilot Study. Issue 4 (February 2020) - Cremone-Caira, Amanda; Root, Helen; Harvey, Elizabeth A.; McDermott, Jennifer M.; Spencer, Rebecca M. C.
Objective: Children with ADHD often have sleep complaints and cognitive deficits. The aim of this pilot study was to determine whether sleep extension improves inhibitory control, a primary cognitive deficit in ADHD.Method: Children with ( n = 11) and without ( n = 15) ADHD participated in a within-subject sleep extension intervention that targeted nocturnal sleep duration. Sleep was assessed with actigraphy and polysomnography. Inhibitory control was assessed with a Go/No-Go task.Results: For children without ADHD, there was a significant main effect of time, such that morning inhibitory control was 10% greater than evening inhibitory control. However, inhibitory control did not differ between the baseline and extension conditions in this group. For children with ADHD, although morning inhibitory control did not differ from evening inhibitory control, sleep extension improved inhibitory control by 13% overall.Conclusion: These results suggest that a sleep extension intervention improves inhibitory control in children with ADHD.